The effectiveness of the Penn Resiliency Programme (PRP) and its adapted versions in reducing depression and anxiety and improving explanatory style: A systematic review and meta‐analysis. (2nd August 2016) - Bastounis, Anastasios; Callaghan, Patrick; Banerjee, Anirban; Michail, Maria
ABSTRACT: Mental health problems in children can be precursors of psychosocial problems in adulthood. The aim of this study is to assess the effectiveness of the universal application of a resilience intervention (PRP and derivatives), which has been proposed for large scale roll‐out. Electronic databases were searched for published randomized controlled trials of PRP and derivatives to prevent depression and anxiety and improve explanatory style in students aged 8–17 years. Studies were meta‐analysed and effect sizes with confidence intervals were calculated. The Quality Assessment Tool for Quantitative Studies of the Effective Public Health Practice Project was used to determine the confidence in the effect estimates. Nine trials from Australia, the Netherlands and USA met the inclusion criteria. No evidence of PRP in reducing depression or anxiety and improving explanatory style was found. The large scale roll‐out of PRP cannot be recommended. The content and structure of universal PRP should be re‐considered.